Value of Lipiodol Computed Tomography and Digital Subtraction Angiography in the Era of Helical Biphasic Computed Tomography as Preoperative Assessment of Hepatocellular Carcinoma - Nakayama, Ataru (2001)
OBJECTIVE: To compare the diagnostic accuracies of Lipiodol computed tomography (CT) and helical biphasic CT as preoperative imaging modalities for hepatocellular carcinoma (HCC). SUMMARY BACKGROUND DATA: Lipiodol CT after digital subtraction angiography has long been used as a highly sensitive imaging modality for HCC. The recent advent of helical CT has allowed scanning the entire liver during both the arterial and portal venous phase of contrast enhancement. METHODS: The authors analyzed data from 164 patients who underwent hepatic resection for HCC to calculate the sensitivity and specificity of these modalities. Findings of intraoperative ultrasonography followed by histologic confirmation were set as the gold standard. RESULTS: Although sensitivity decreased with both modalities as tumors became small and well differentiated, helical CT showed a higher sensitivity than Lipiodol CT in detecting well-differentiated HCC nodules smaller than 2 cm. In contrast, Lipiodol CT was superior to helical CT for the detection of small but moderately to poorly differentiated nodules. The overall sensitivity of helical CT was higher than that of Lipiodol CT. These findings suggest that helical CT is superior in delineating early HCC, whereas Lipiodol CT is specific to the detection of intrahepatic metastases. In terms of specificity, helical CT was superior to Lipiodol CT. CONCLUSIONS: Helical CT and Lipiodol CT are complementary modalities. At present, helical biphasic CT does not obviate the need for invasive techniques such as angiography and Lipiodol CT as preoperative examinations for HCC.